The factors discriminating the results of screening test aimed at detection of scoliosis and detection of flexibility disorders in group of preterm children at the beginning of school age - Piwoński, Paweł; Perenc, Lidia; Walicka-Cupryś, Katarzyna; Zajkiewicz, Katarzyna; Rachwał, Maciej; Drzał-Grabiec, Justyna; Przygoda, Łukasz; Cyran-Grzebyk, Barbara; Hudáková, Zuzana; Czarnecki, Piotr (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
Introduction. The threshold of compulsory schooling for prematurely born children is of particular importance. It’s a period of intense physical development which may increase the risk of scoliosis. Aim. The aim of this research is to determine whether age, gender, BMI value and selected elements of perinatal interview discriminate the results of screening test aimed at detection of scoliosis and flexibility disorders in group of preterm children at the beginning of school age. Material and methods. The study population consisted of 61 preterm children aged 5–8 years. The study included perinatal interview, BMI assessment, screening tests to detect scoliosis and flexibility. Results. Statistically significant dependence was obtained between age and normal and abnormal results of the screening test aimed at detection of scoliosis and between the result of the screening test for detecting flexibility disorders and: age, number of foetuses, assessment on the Apgar scale. Conclusion. The results of screening test aimed at occurrence of scoliosis in group of preterm children are significantly correlated with the age and screening test aimed at occurrence of the flexibility disorders are discriminated by age, origin from monoor multi-foetus pregnancy and assessment on the Apgar scale.
Keywords: development of premature babies; health balance; prematurity; school readiness